2019
DOI: 10.1097/gme.0000000000001416
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial comparing vaginal laser therapy to vaginal estrogen therapy in women with genitourinary syndrome of menopause: The VeLVET Trial

Abstract: Objective: The aim of the study was to compare 6-month efficacy and safety for treatment of vaginal dryness/genitourinary syndrome of menopause in women undergoing fractionated CO2 vaginal laser therapy to women using estrogen vaginal cream. Methods: This multicenter, randomized trial compared fractionated CO2 laser to estrogen cream at 6 institutions. We included menopausal women with significant vaginal atrophy symptoms and we excluded women with prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
126
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(133 citation statements)
references
References 31 publications
7
126
0
Order By: Relevance
“…In fact, the use of local estrogens is supported by the evidence of superiority over placebo in several trials, for both clinical and cytological outcomes [46,47]. About improvement in symptoms, few studies compared fractional CO 2 laser to local estrogens [48–51]. These studies showed similar results between the two treatments [48,51], or even better results for the fractional CO 2 laser (alone or in combination with local estrogens) [49,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the use of local estrogens is supported by the evidence of superiority over placebo in several trials, for both clinical and cytological outcomes [46,47]. About improvement in symptoms, few studies compared fractional CO 2 laser to local estrogens [48–51]. These studies showed similar results between the two treatments [48,51], or even better results for the fractional CO 2 laser (alone or in combination with local estrogens) [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…About improvement in symptoms, few studies compared fractional CO 2 laser to local estrogens [48–51]. These studies showed similar results between the two treatments [48,51], or even better results for the fractional CO 2 laser (alone or in combination with local estrogens) [49,50]. In addition, another study showed that the fractional CO 2 laser was effective in women dissatisfied with previous local estrogens [52].…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing the full‐text articles, an additional 20 records were excluded. This process resulted in 49 articles, 1,2,4,13‐58 which were further reviewed using a hand‐searching approach. Table 2 displays all the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…Laser, whose efficacy has been very recently confirmed in the general population of VVA patients by the VeLVET trial [15], is viewed favorably by all Delphi Panel members but, in their practices, it is seldom used for cost reasons.…”
Section: Resultsmentioning
confidence: 99%